(untitled) (Journal of the College of Education for Women, 2019)
This research seeks to give an objective, neutral and all-embracing examination of the prince ((Faker al Deen Almani)) as historical study , the prince regard as an important person for his active role in the Lebanese political system from 1590 till 1697. This research include three aspects , chapter 1 deals with historical inheritance of Lebanon before Amaaniya Amart and a rise of Amaanya Amart from (1516-1697). Chapter 2 devoted to the study of personality of Alamer Faker al Deen Al-Mani and his internal policy , Chapter 3 studies the foreign policy of the prince in Lebanon and his end , Finally in the conclusion , certain findings clearly summarized.